Penerapan E-Procurement Dalam Mendukung Layanan Pengadaan Barang Dan Jasa Di Dinas Pekerjaan Umum Dan Penataan Ruang Kota Tangerang - Nurhasan, Widia; Hilman, Hilman; Firdiyani, Fitria (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Electronic procurement of goods and services, or e-procurement, enables innovation in government and leverages technology platforms to obtain better information, better cost performance, greater efficiency, and maximize the effectiveness of e-procurement. It is an information system that transforms. The purpose of this study is to determine the